Is youtube qualified as an information source for regenerative endodontics - DURMAZPINAR, PARLA MEVA (My University, 2022)
Objective: This study assessed the educational quality and reliability of YouTube videos about regenerative endodontics. Materials and Methods: The YouTube videos were viewed using the searching terms ‘regenerative endodontic treatment’, ‘endodontic regeneration’, ‘pulp regeneration’, ‘pulp revascularization’, and ‘pulp revitalization’. The first 60 videos (300 videos, in total) were searched for each term and after initial screening, 70 videos were selected for analysis by three reviewers according to the inclusion criteria. The global score for educational value and modified DISCERN score was used to evaluate the quality and reliability of the videos. Kruskal-Wallis test and chi-square test were used to analyze data. Correlations analyzed using PearsonSpearman test. Results: The mean of Modified DISCERN score of the YouTube videos about regenerative endodontics was 3.02±1.07 which was categorized as moderate reliability. The mean of global score for educational value of the videos was 2.05±1.13 and 37.1% (n=26) of them were in a poor quality while 14.3% (n=10) were in a good quality due to the scoring of this value. No excellent quality video was found. Conclusion: It can be concluded that the amount of educational and reliable information on YouTube videos about regenerative endodontics is limited.

Amaç: Bu çalışma, rejeneratif endodonti ile ilgili YouTube videolarının eğitim kalitesini ve güvenilirliğini değerlendirmeyi amaçlamaktadır. Gereç ve Yöntemler: Bu çalışmada ‘rejeneratif endodontik tedavi’, ‘endodontik rejenerasyon’, ‘pulpa rejenerasyonu’, ‘pulpa revaskülarizasyonu’ ve ‘pulpa revitalizasyonu’ arama terimleri kullanılarak ilgili YouTube videoları görüntülendi. Her bir terim için ilk 60 video (toplam 300 video) tarandı ve ilk taramada dahil edilme kriterlerine göre seçilen 70 video üç gözlemci tarafından analiz edildi. Videoların kalitesi ve güvenilirliğini değerlendirmek amacıyla ‘eğitim değeri global skoru’ ve ‘modifiye DISCERN skoru’ kullanıldı. Verilerin analizi için Kruskal Wallis ve ki-kare testleri kullanıldı. Veriler arasındaki korelasyonlar Pearson-Spearman testi kullanılarak analiz edildi. Bulgular: Rejeneratif endodonti ile ilgili YouTube videolarının Modifiye DISCERN puanlama ortalaması 3,02±1,07 olup, ortalama güvenilirlik olarak kategorize edildi. Videoların global eğitim değeri puanlama ortalaması 2,05±1,13 olarak bulunmuş olup, bu puanlamaya göre %37,1’inin (n=26) kötü kalitede, %14,3’ünün (n=10) iyi kalitede olduğu görüldü. Videoların hiçbiri mükemmel kalitede bulunmadı. Sonuç: YouTube videolarında rejeneratif endodonti ile ilgili eğitici ve güvenilir bilgi miktarının sınırlı olduğu görülmektedir.
Youtube rejeneratif endodonti için nitelikli bir bilgi kaynağı mı
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Educational quality; endodontic regeneration; regenerative endodontic treatment; YouTube; PULP; QUALITY; VIDEOS; TEETH; Educational quality; endodontic regeneration; regenerative endodontic treatment; YouTube; Eğitim kalitesi; endodontik rejenerasyon; rejeneratif endodontik tedavi; YouTube